2020
DOI: 10.1177/0253717620928728
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Experiences of Aggressive Persons with Schizophrenia

Abstract: Background: Understanding the caregivers’ experiences of aggressive persons with mental disorders is very important from the public health point of view. Only a few Indian studies have focused on this. No Indian studies could be found that explored the caregivers’ experiences of aggressive persons with schizophrenia. This study was conducted to explore the same. Methods: A qualitative phenomenological study was conducted in the outpatient and inpatient settings at a tertiary care mental health institute at Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Similarly, in a study conducted with caregivers of patients with chronic mental illness, similar to our study, it was stated that the role of caregiver is a difficult and unpredictable experience that requires effort and that the quality of life of caregivers is adversely affected (Saunders & Byrne, 2002). It is seen that similar results have been reached in many studies in the literature (Akgül Gök & Duyan, 2020; Doval et al, 2018; Neha et al, 2021; Ohaeri, 2003; Zimmerman, 1995). The most important source of social support for caregivers throughout the process is their families.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, in a study conducted with caregivers of patients with chronic mental illness, similar to our study, it was stated that the role of caregiver is a difficult and unpredictable experience that requires effort and that the quality of life of caregivers is adversely affected (Saunders & Byrne, 2002). It is seen that similar results have been reached in many studies in the literature (Akgül Gök & Duyan, 2020; Doval et al, 2018; Neha et al, 2021; Ohaeri, 2003; Zimmerman, 1995). The most important source of social support for caregivers throughout the process is their families.…”
Section: Discussionsupporting
confidence: 87%
“…Ganguly et al (2010) stated in the study that the caregiver could never leave their child’s side, and that at least one person should be with them, and that this situation triggers the feeling of loneliness and isolation over time and that it can be expressed with negative emotional states such as anger and resentment. Neha et al (2021), in his study with caregivers, stated that one of the participants used violence from time to time due to his child’s aggressive behavior and later regretted it. Although the extent and state of anger varies, many studies with caregivers have found results consistent with the results of our study (Akgül Gök & Duyan, 2020; Brain et al 2018; Koschorke et al 2017; Lima & de Andrade Lima, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It is needed to care, support, and train the caregivers regarding handling of aggressive patient. 23 Caregivers only take care of their physical illnesses, mental issues aroused during caring of their mentally ill patient, facing aggression of their patient often neglected. Maladaptive coping strategies and lack of knowledge regarding dealing of aggression of mentally ill patient not only cause suffering to the caregivers but also worsen the aggression and hinder the recovery of the patient.…”
Section: Introductionmentioning
confidence: 99%